Teaching Techniques for Writing Skills in the Eleventh Grade of MAN 2 Bukittinggi in the 2018/2019 Academic Year - Wike Fauza Islami; Merry Prima Dewi (YASIN, 2026)
This study examines the teaching techniques used by English teachers in teaching writing skills to eleventh-grade students of MAN 2 Bukittinggi in the 2018/2019 academic year. This study was motivated by students’ problems in writing, such as lack of vocabulary, weak mastery of grammar, and low learning motivation, as well as teachers’ challenges in motivating students, limited instructional time, and differences in students’ ability levels. This study aims to identify and describe the teaching techniques used by teachers in writing instruction. This study used a qualitative approach with a descriptive design. The research subjects consisted of two eleventh-grade English teachers at MAN 2 Bukittinggi. Data were collected through classroom observation, interviews, and document analysis in the form of lesson plans, syllabi, and learning materials. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing and verification, whereas data validity was obtained through methodological triangulation. The results showed that the teachers used various techniques in writing instruction, namely programmed learning, writing based on topic, microteaching, writing based on picture, dictation, fill in the blank, writing based on template, and joint writing in a group. The first teacher more dominantly used a combination of programmed learning and writing based on topic, whereas the second teacher more frequently applied microteaching and writing based on topic. These techniques helped students become more active, interested, and confident in writing activities. The conclusion of this study emphasizes that variations in teaching techniques make a positive contribution to students’ understanding and participation in writing instruction. The implications of this study indicate the importance of applying flexible and innovative learning techniques for English teachers to improve students’ writing skills and create a more effective and engaging learning process.